The Influence of the Spread of Islam in Southeast Asia on Cultural Identity Policies in the Era of Globalization - Luthfiah, Luthfiah (Islamic Civilization and History, 2024)
The spread of Islam in Southeast Asia has played an important role in the formation of cultural identity in the region, especially amid the challenges of globalization that threaten traditional values. This research aims to analyze how Islamic values influence cultural identity policies in Southeast Asian countries in the modern context. The method used in this research is a qualitative approach with document analysis, which includes historical texts, government policies, and related academic literature. The results show that Islamic values serve as the foundation for cultural identity policies, which include Islamic-based education, protection of cultural heritage, and community strengthening. In addition, the study found that such policies are often designed to address the negative influences of globalization while strengthening local identities. This research underscores the importance of integrating Islamic values in policies to maintain the integrity of cultural identity in Southeast Asia.